The welfare effects and distributional impacts of road user charges on commuters: An empirical analysis of Dresden - Ulf Teubel (European Regional Science Association (ERSA), 1998)
Congestion, air pollution and noise are perceived as some of the most pressing problems caused by increasing use of the car in urban areas today. The introduction of road user charges (road pricing) is a common proposal to solve or reduce these problems. However, its public acceptance is rather low, because it is considered as unjust. Therefore this study investigates the equity issue of road user charges in detail and analyses the distribution of costs and benefits among different groups. One group particularly affected by road pricing and analytically separable is the group of commuters. Hence, this paper analyses empirically the issue of the distributional impacts of road user charges for this group. After specifying the decision of the commuters within a microeconomic framework a binary logit model for mode choice was developed and estimated with disaggregated work trip data from Dresden. Then measures of users benefit that have been derived for discrete choice demand models were applied to the estimated demand functions for the different modes. So it was possible to calculate the changes in commuters welfare for the introduction of different simple toll schemes. This was done for commuters from different income groups and different areas within Dresden. Finally, measures of inequality for situations with and without road pricing were compared.
Keywords: 330